Optical glass and optical element

By introducing Nb5+ and optimizing oxide components in fluorophosphate glass, the volatility and chemical durability of fluorophosphate glass in high-temperature processes are solved, and high relative partial dispersion and chemical durability are achieved, which is suitable for high-quality Optical components.

CN119118508APending Publication Date: 2024-12-13HOYA CORPORATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411387909.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2018-03-22
Filing Date
2018-03-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Fluorophosphate glass is prone to volatile problems in high-temperature processes, resulting in changes in optical properties and reduced glass uniformity. At the same time, potential scars are enlarged during polishing, affecting surface quality.

Method used

By introducing Nb5+ and optimizing oxide components, an optical glass with high relative partial dispersion and chemical durability is formed. Nb5+ is combined with the -O-P-O- structure to reduce volatileness and verified chemical durability by immersion test of NaOH aqueous solution.

Benefits of technology

It effectively reduces the volatility of fluorophosphate glass in high-temperature processes, improves its chemical durability and optical properties, and is suitable for chromatic aberration correction optical components, ensuring high-quality optical surfaces.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118508A_ABST
    Figure CN119118508A_ABST
Patent Text Reader

Abstract

The present invention provides an optical glass and an optical element, the optical glass containing P < 5 + >, Al < 3 + >, Nb < 5 + >, O < 2-> and F <-> as essential components, the molar ratio of the content of Al < 3 + > to the content of P < 5 + > (Al < 3 + > / P < 5 + >) being 0.30 or more, the content of Nb < 5 + > being 1.0 cation% or more, the content of O < 2-> being 10-85 anion%, the content of F <-> being 15-90 anion%, and the molar ratio of the content of O < 2-> to the total content of P < 5 + > and Nb < 5 + > (O < 2-> / (P < 5 + > + Nb < 5 + >) being 3.0 or more.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of the invention patent application with application number 201810292798.X. The application date of the original application is March 30, 2018, and the name of the invention is “Optical Glass and Optical Elements”. Technical Field

[0002] The present invention relates to optical glass and optical elements. Background Art

[0003] Fluorophosphate glass containing phosphorus, oxygen, and fluorine is widely known as an optical glass having low dispersion and showing positive anomalous dispersion.

[0004] Since fluorophosphate glass has the above-mentioned excellent optical characteristics, it has high utilization value as an optical element material for correcting high-order chromatic aberrations.

[0005] Examples of such fluorophosphate glass are described in Patent Documents 1 to 4.

[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-112717;

[0007] Patent Document 2: Japanese Patent Application Publication No. 2013-151410;

[0008] Patent document 3: Japanese Patent Publication No. 51-114412;

[0009] Patent document 4: Japanese Patent Application Laid-Open No. 58-217451.

[0010] Problem that the invention aims to solve

[0011] As described above, fluorophosphate glass has excellent optical properties, but it shows significant volatility in the high-temperature process of melting and molding the glass. Volatilization from the glass melt during the melting and molding process may cause phenomena such as glass deterioration, changes in optical properties, and reduction in glass uniformity.

[0012] In addition, in the process of grinding and polishing the glass material formed by optical glass to make optical elements such as lenses and prisms, the polished glass is usually cleaned. On the other hand, on the surface of the polished glass, there are usually tiny scratches called latent scratches that are invisible to the eye. However, when the surface of the glass is eroded by cleaning, sometimes the latent scratches expand and appear to become a source of light scattering, and the surface quality of the glass is reduced. In addition, sometimes the surface quality of the glass is reduced due to the deterioration of the glass surface caused by cleaning.

[0013] In order to suppress the above-mentioned reduction in the surface quality of the fluorophosphate glass, it is desired to improve the chemical durability of the fluorophosphate glass. Summary of the invention

[0014] An object of one embodiment of the present invention is to provide an optical glass having a large relative partial dispersion and suitable for chromatic aberration correction while reducing the volatility of fluorophosphate glass in a high-temperature process; and an optical element formed of the optical glass.

[0015] Another aspect of the present invention aims to provide an optical glass made of fluorophosphate glass which has excellent chemical durability, large relative partial dispersion, and is suitable for chromatic aberration correction; and an optical element made of the optical glass.

[0016] Solutions for solving problems

[0017] One embodiment of the present invention relates to

[0018] An optical glass (hereinafter also referred to as "optical glass 1") comprising P 5+ 、Al 3+ , Nb 5+ , O 2- and F - As a necessary ingredient,

[0019] Al 3+ The content relative to P 5+ The molar ratio of the content (Al 3+ / P 5+ ) is 0.30 or more,

[0020] Nb 5+ The content of cation is 1.0% or more,

[0021] O 2- The content of anion is 10~85%

[0022] F - The content of anion is 15-90%,

[0023] O 2- The content relative to P 5+ and Nb 5+ The molar ratio of the total content (O 2- / (P 5+ +Nb 5+ )) is above 3.0.

[0024] The optical glass preferably has positive anomalous dispersion.

[0025] As an index of positive anomalous dispersion, the relative partial dispersion Pg, F can be used. The relative partial dispersion Pg, F is expressed as follows using the refractive index nF at the F line (wavelength 486.13nm), the refractive index nC at the C line (wavelength 656.27nm), and the refractive index ng at the g line (wavelength 435.84nm).

[0026] Pg,F=(ng-nF) / (nF-nC)···(1)

[0027] It is known that the intrinsic absorption wavelength of Nb contained in the glass in the ultraviolet region is close to the visible light region, and the absorption intensity is also large. As a result, the wavelength dispersion of the refractive index shows a tendency to be highly dispersed. That is, the refractive index difference nF-nC between the F line and the C line increases, and the Abbe number νd decreases. On the other hand, the refractive index difference ng-nF between the g line and the F line also increases.

[0028] Here, if the effect of increasing ng-nF is greater than the effect of increasing nF-nC, it can be seen from formula (1) that Pg,F increases.

[0029] Focusing on this point, the present inventors have found that the introduction of Nb as a glass component can significantly increase the relative partial dispersion Pg,F while maintaining low dispersion (large νd) in the same range as that of conventional fluorophosphate glasses.

[0030] However, in the melting process of fluorophosphate glass containing Nb, Nb is easily volatilized from the glass melt. When Nb and F are combined during the melting process, niobium fluoride is generated. Niobium fluoride has a high vapor pressure and is easily volatilized from the glass melt.

[0031] The present inventors have conducted intensive studies to prevent Nb introduced for improving relative partial dispersion from promoting volatilization, and have obtained the following findings.

[0032] It can be considered that P 5+ It exists in the glass in the form of -OPO- structure, which helps to form the glass network. 5 + Nb with equal valence 5+ It also contributes to the network formation of the glass by occupying the P position in the -OPO- structure.

[0033] It can be considered that when Nb 5+ When introduced into the network structure, niobium fluoride having a high vapor pressure is less likely to be generated, resulting in a decrease in the volatility of the glass.

[0034] However, in order to 5+ Introduced into the network structure, a sufficient number of O 2- When considering Nb 5+If O 2- The content of cations (P 5+ and Nb 5+ The molar ratio of the total content of 2- / (P 5+ +Nb 5 + )) is 3.0 or more, then Nb 5+ It is easy to be incorporated into the network, thereby being able to suppress an increase in volatility.

[0035] The present inventors have completed the optical glass according to one embodiment of the present invention described above based on the above-mentioned findings.

[0036] Another aspect of the present invention relates to

[0037] An optical glass formed of fluorophosphate glass,

[0038] The mass reduction per unit area when immersed in NaOH aqueous solution for 15 hours D Na OH Less than 0.25mg / (cm 2 15h), and

[0039] The Abbe number νd and the relative partial dispersion Pg,F satisfy the following equation (4):

[0040] Pg,F>-0.0004νd+0.5718···(4)

[0041] Effects of the Invention

[0042] According to one embodiment of the present invention, it is possible to provide an optical glass having a large relative partial dispersion and suitable for chromatic aberration correction while reducing the volatility of fluorophosphate glass in a high-temperature process; and it is possible to provide an optical element formed of the optical glass.

[0043] According to another aspect of the present invention, it is possible to provide an optical glass that has a large relative partial dispersion as a fluorophosphate glass, is suitable for chromatic aberration correction, and has excellent chemical durability; and it is possible to provide an optical element formed of the optical glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 The optical characteristics of the optical glass of the embodiment are shown in the graph of Abbe number νd-refractive index nd.

[0045] Figure 2 The optical characteristics of the optical glass of the embodiment and the optical characteristics of the conventional optical glass in the figure showing Abbe number νd-relative partial dispersion Pg,F. DETAILED DESCRIPTION

[0046] In the present invention and this specification, the content and total content of cationic components are expressed as cation % unless otherwise specified, and the content and total content of anionic components are expressed as anion % unless otherwise specified.

[0047] Here, "cation %" refers to a value calculated as "(number of cations of interest / total number of cations in glass component)×100", and means the molar percentage of the amount of cations of interest relative to the total amount of cation components.

[0048] Furthermore, “anion %” refers to a value calculated as “(number of anions of interest / total number of anions in glass component)×100”, and means the molar percentage of the amount of anions of interest relative to the total amount of anion components.

[0049] The molar ratio of the contents of the cationic components is equal to the content ratio of the cationic components of interest expressed in cation %, and the molar ratio of the contents of the anionic components is equal to the content ratio of the anionic components of interest expressed in anion %.

[0050] The molar ratio of the content of the cationic component to the content of the anionic component is the ratio of the contents (expressed in mol %) of the components of interest when the total amount of all cationic components and all anionic components is taken as 100 mol %.

[0051] The content of each component can be quantified by a known method such as inductively coupled plasma atomic emission spectrometry (ICP-AES), inductively coupled plasma mass spectrometry (ICP-MS), ion chromatography, or the like.

[0052] In the present invention and this specification, "fluorophosphate glass" refers to glass containing at least phosphorus, oxygen, and fluorine as elements constituting glass.

[0053] [Optical glass 1]

[0054] <Glass composition>

[0055] Hereinafter, an optical glass 1 which is one embodiment of the present invention will be described.

[0056] P 5+ It has the function of being a network forming component. 3+ It is a component that plays a role in maintaining the thermal stability of glass and improving chemical durability and processability. From the perspective of maintaining the thermal stability of glass well, Al 3+ The content relative to P 5+ The molar ratio of the content (Al 3+ / P 5+ ) is 0.30 or more. From the perspective of increasing the refractive index while maintaining the Abbe number, the molar ratio (Al3+ / P 5+ ) is effective when it is set to 0.30 or more.

[0057] Molar ratio (Al 3+ / P 5+ On the other hand, from the perspective of maintaining the thermal stability of the glass well, the molar ratio (Al 3+ / P 5+ ) has a preferred upper limit of 2, and a more preferred upper limit of 1.

[0058] Nb 5+ With P 5+ Together with Nb, it maintains the thermal stability of the glass and increases the relative partial dispersion. 5+ The content of Nb is 1.0% or more. 5+ The preferred lower limit of the content of Nb is 1.5%, the more preferred lower limit is 2%, the further preferred lower limit is 2.5%, and the further preferred lower limit is 3%. 5+ When the content of Nb is excessive, the volatility of the glass during melting becomes significant, and the homogeneity of the glass tends to decrease. 5+ The upper limit of the content of Nb is preferably 15%, more preferably 13%, and still more preferably 10%. 5+ The relationship with the chemical durability of glass will be described later.

[0059] From the perspective of maintaining the thermal stability of glass, P 5+ and Nb 5+ The total content (P 5+ +Nb 5+ ) is preferably 15% or more. 5+ and Nb 5+ The total content (P 5+ +Nb 5+ ) is preferably 20%.

[0060] O 2- It has the function of maintaining the thermal stability of glass. In order to achieve this effect, O 2- The content of anions is 10% or more. 2- When the content of anion is more than 85%, F - The content of is insufficient, and it is difficult to obtain low dispersion. 2- The content of anion is 10-85%. 2- The preferred lower limit of the content is 20%, a more preferred lower limit is 30%, a preferred upper limit is 80%, a more preferred upper limit is 75%, a further preferred upper limit is 70.93%, and a further preferred upper limit is 70%.

[0061] F - It has the effect of reducing the dispersion of glass and imparting abnormal dispersion, lowering the glass transition temperature, and improving chemical durability. - When the content of F is less than 15% anion, it is difficult to obtain the above effect. - When the content of F exceeds 90% anion, it is difficult to maintain the thermal stability of the glass. - When the content is excessive, the D NaOH , D STPP , D 0 The values ​​of tend to increase.

[0062] From the above point of view, F - The content of anion is 15-90%. - The preferred lower limit of the content is 20%, a more preferred lower limit is 25%, a further preferred lower limit is 28.86%, a further preferred lower limit is 30%, a preferred upper limit is 80%, and a more preferred upper limit is 70%.

[0063] As mentioned above, the reduction of Nb 5+ From the perspective of increased volatilization in the glass melt, O 2- The content relative to P 5+ and Nb 5+ The molar ratio of the total content (O 2- / (P 5+ +Nb 5+ )) is 3.0 or more. 2- / (P 5+ +Nb 5+ The preferred lower limit of the molar ratio (O) is 3.2. 2- / (P 5+ +Nb 5 + The preferred upper limit of )) is 4.0, and the more preferred upper limit is 3.8.

[0064] Alkaline earth metal components, namely Mg 2+ , Ca 2+ , Sr 2+ And Ba 2+ It is a component that plays a role in adjusting the viscosity and refractive index of the glass and improving the thermal stability. In order to obtain the above effects, the total content of the alkaline earth metal components is preferably R 2+ (Mg 2+ +Ca 2+ +Sr 2+ +Ba 2+) is 20 cation % or more, more preferably 30 % or more, and further preferably 35 % or more.

[0065] On the other hand, when the total content of alkaline earth metal components R 2+ When the content is excessive, the thermal stability tends to decrease. Therefore, the total content of the alkaline earth metal components is preferably R 2+ Less than 50%. 2+ A more preferred upper limit is 45%, and a further preferred upper limit is 40%.

[0066] The above optical glass may also contain one or more selected from La 3+ , Gd 3+ , Y 3+ 、Lu 3+ Yb 3+ Rare earth components.

[0067] From the perspective of suppressing the increase in specific gravity of the glass and reducing dispersion for a certain refractive index, La is preferred. 3+ , Gd 3+ , Y 3+ 、Lu 3+ Yb 3+ Total content (La 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ ) relative to Al 3+ The molar ratio of the content (La 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ ) / Al 3+ ) is less than 0.3. 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ ) / Al 3+ The more preferred upper limit of ) is 0.2, and the further preferred upper limit is 0.1. 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ ) / Al 3+ ) can also be 0.

[0068] Next, the content of each component will be described.

[0069] P 5+It is an essential component for forming a glass network. From the perspective of maintaining good thermal stability, P 5+ The preferred lower limit of the content of is 5%, the more preferred lower limit is 10%, and the further preferred lower limit is 20%. From the perspective of maintaining good chemical durability, maintaining low dispersion and abnormal partial dispersion, P 5+ The preferred upper limit of the content is 40%, a more preferred upper limit is 38%, and a further preferred upper limit is 35%.

[0070] Al 3+ It is an essential component that plays a role in improving thermal stability, chemical durability, and processability, and also plays a role in increasing the refractive index. 3+ The preferred lower limit of the content of Al is 5%, the more preferred lower limit is 7%, the further preferred lower limit is 9%, and the further preferred lower limit is 11%. 3+ The preferred upper limit of the content is 40%, a more preferred upper limit is 38%, a further preferred upper limit is 36%, and a further preferred upper limit is 34%.

[0071] In the glass composition expressed in atomic %, O 2- The content relative to Al 3+ The content ratio of O 2- / Al 3+ Preferably less than 12, more preferably less than 10, further preferably less than 8. 2- When the content of F is too high, - The content of Al is relatively reduced, showing a tendency to increase the glass transition temperature. On the other hand, as described above, from the perspective of improving thermal stability, chemical durability, and processability, and having desired optical properties, Al 3+ It is a useful component. In order to obtain sufficient Al 3+ In order to suppress the increase of the glass transition temperature under the effect of 2- The content relative to Al 3+ The content ratio of O 2- / Al 3+ The above range is obtained. 3+ From the viewpoint of the decrease in devitrification resistance caused by the relative increase in the content of 2- / Al 3+ The lower limit of can be, for example, 2 or more or 3 or more as a benchmark.

[0072] The content of each component in the glass composition expressed in atomic % can be calculated as a value expressed in mole percentage when the total content of all cationic components and all anionic components is taken as 100 mol %.

[0073] Mg 2+ , Ca 2+ , Sr 2+ , Ba 2+ The preferred content of each component is as follows.

[0074] Mg 2+ The content of is preferably in the range of 0 to 10%, and more preferably in the range of 0 to 8%.

[0075] Ca 2+ The content of is preferably in the range of 0 to 20%, more preferably in the range of 0 to 15%.

[0076] Sr 2+ The preferred range of the content is 0 to 40%, and the more preferred range is 0 to 30%.

[0077] Ba 2+ The preferred lower limit of the content is 5%, and a more preferred lower limit is 10%. The preferred upper limit is 50%, and a more preferred upper limit is 40%.

[0078] La 3+ , Gd 3+ , Y 3+ 、Lu 3+ The preferred contents of each are as follows.

[0079] La 3+ The preferred range of the content is 0 to 5%, and the more preferred range is 0 to 3%.

[0080] G 3+ The preferred range of the content is 0 to 5%, and the more preferred range is 0 to 3%.

[0081] Y 3+ The preferred range of the content is 0 to 5%, and the more preferred range is 0 to 3%.

[0082] Lu 3+ The preferred range of the content is 0 to 5%, and the more preferred range is 0 to 3%.

[0083] Yb 3+ Since Yb ​​has light absorption in the infrared region, it is not preferred for imaging based on infrared light. 3+ The content of Yb is preferably expressed as the molar ratio of the total content of other rare earth components (Yb 3+ / (La 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ )) is limited by the following method. That is, it is preferred that Yb3+ The content relative to La 3+ , Gd 3+ , Y 3+ 、Lu 3+ Yb 3+ The molar ratio of the total content (Yb 3+ / (La 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ )) is set to 0.5 or less, more preferably to 0.1 or less, and further preferably to 0 (Yb 3+ The content is 0%).

[0084] Zn 2+ It has the effect of improving thermal stability while maintaining the refractive index. However, when it is contained in excessive amounts, the dispersion becomes high and it is difficult to obtain the desired optical properties. 2+ The content of Zn is preferably in the range of 0 to 10%. 2+ The more preferred upper limit of the content of Zn is 8%, and the further preferred upper limit is 5%. 2+ The content can also be 0%.

[0085] The alkali metal component is a cationic component that has the function of adjusting the viscosity of the glass and improving the thermal stability. + If the amount is excessive, the thermal stability will decrease. + The preferred range of R is 0 to 30%. + A more preferred range is 0 to 20%, and a further preferred range is 0 to 15%. + The upper limit of is more preferably 10%, more preferably 8%, and more preferably 7%. + When there is excess, D STPP and D 0 Therefore, from the perspective of imparting excellent chemical durability to the glass, it is preferred that R + is the above range.

[0086] On the other hand, from the viewpoint of lowering the glass transition temperature, R + The preferred lower limit is 1%, the more preferred lower limit is 2%, and the further preferred lower limit is 3%.

[0087] As the alkali metal component R + , which can show that Li + 、Na + , K + , Rb+ , Cs + . Rb + , Cs + Compared with other alkali metal components, it tends to increase the specific gravity of glass.

[0088] Therefore, Rb + The content of is preferably 0 to 3%, more preferably 0 to 2%, further preferably 0 to 1%, and may be 0%.

[0089] Cs + The content of is preferably 0 to 3%, more preferably 0 to 2%, further preferably 0 to 1%, and may be 0%.

[0090] From the perspective of maintaining the thermal stability of glass, Li + The content of is preferably in the range of 0 to 30%, more preferably in the range of 2 to 20%, and still more preferably in the range of 4 to 10%.

[0091] From the perspective of maintaining the thermal stability of glass, Na + The content of is preferably in the range of 0 to 10%, more preferably in the range of 0 to 8%, and still more preferably in the range of 0 to 6%.

[0092] From the perspective of maintaining the thermal stability of glass, K + The content of is preferably in the range of 0 to 10%, more preferably in the range of 0 to 8%, and still more preferably in the range of 0 to 6%.

[0093] Si 4+ Even if it is contained in a small amount, it can be contained, but if it is contained in an excessive amount, the solubility and thermal stability will decrease. 4+ The content of is preferably in the range of 0 to 5%, more preferably in the range of 0 to 3%, further preferably in the range of 0 to 1%, and may be 0%.

[0094] B 3+ Even if contained in a small amount, it shows significant volatility. In order not to promote volatility, it is preferred to 3+ The content of B is set to 2% or less. 3+ The content of is preferably in the range of 0 to 1%, more preferably in the range of 0 to 0.1%, and still more preferably 0%.

[0095] When molten glass flows out of a tube installed in a glass melting device, in order to suppress the wetting of the outer periphery of the tube by the molten glass and suppress the deterioration of the glass quality due to wetting, Cl is contained. - It is effective. - The content of Cl is preferably in the range of 0 to 1%, more preferably in the range of 0 to 0.5%, and still more preferably in the range of 0 to 0.3%.- It also acts as a clarifying agent.

[0096] In addition, a small amount of Sb can be added 3+ 、Ce 4+ The total amount of the clarifier can be 0% or more, and is preferably less than 1%. For example, Sb 3+ and Ce 4+ The total content of can be 0% or more, and is preferably less than 1%.

[0097] Pb, Cd, As, and Th are components that may cause environmental burdens.

[0098] Therefore, it is preferred that the optical glass 1 substantially does not contain at least one of Pb, Cd, As, and Th.

[0099] Pb 2+ The content of Pb is preferably 0 to 0.5%, more preferably 0 to 0.1%, further preferably 0 to 0.05%, and it is particularly preferred that the Pb content is substantially free of 2+ .

[0100] Cd 2+ The content of Cd is preferably 0 to 0.5%, more preferably 0 to 0.1%, further preferably 0 to 0.05%, and it is particularly preferred that the Cd content is substantially free of 2+ .

[0101] As 3+ The content of As is preferably 0 to 0.1%, more preferably 0 to 0.05%, further preferably 0 to 0.01%, and it is particularly preferred that As is substantially not contained. 3+ .

[0102] Th 4+ The content of Th is preferably 0 to 0.1%, more preferably 0 to 0.05%, further preferably 0 to 0.01%, and particularly preferably substantially free of Th. 4+ .

[0103] The optical glass 1 is preferably capable of showing high transmittance over a wide range of the entire visible light region. In order to effectively utilize such an advantage, it is preferred that the optical glass does not contain a colorant. Examples of colorants include Cu, Co, Ni, Fe, Cr, Eu, Nd, Er, and V. The optical glass 1 is preferably substantially free of at least one of Cu, Co, Ni, Fe, Cr, Eu, Nd, Er, and V. The range of the content of Cu, Co, Ni, Fe, Cr, Eu, Nd, Er, and V expressed as cation % is preferably less than 100 ppm for any element, more preferably 0 to 80 ppm, further preferably 0 to 50 ppm or less, and particularly preferably substantially free of any element. Here, ppm is cation ppm.

[0104] In addition, Hf, Ga, Ge, Te, and Tb are expensive components. Therefore, the optical glass 1 preferably does not substantially contain at least one of Hf, Ga, Ge, Te, and Tb. The range of the content of Hf, Ga, Ge, Te, and Tb expressed as cation % is preferably 0 to 0.1% for each element, more preferably 0 to 0.05%, further preferably 0 to 0.01%, further preferably 0 to 0.005%, further preferably 0 to 0.001%, and particularly preferably does not substantially contain.

[0105] The above optical glass can exhibit various characteristics without introducing Hf, Ga, Ge, Te, or Tb.

[0106] <Glass Characteristics>

[0107] (Abbe number νd, refractive index nd)

[0108] In the optical glass 1, from the perspective of effectively utilizing the anomalous partial dispersion, the Abbe number νd is preferably in the range of 45 or more.

[0109] The Abbe number νd is a value indicating a property related to dispersion, and is expressed as νd=(nd-1) / (nF-nC) using the refractive indices nd, nF, and nC at the d-line, F-line, and C-line, respectively.

[0110] The preferred upper limit of the Abbe number νd is 80, and a more preferred upper limit is 70. On the other hand, the preferred lower limit of the Abbe number νd is 45, a more preferred lower limit is 50, and a further preferred lower limit is 55 in order to effectively utilize low dispersion.

[0111] Furthermore, by making the refractive index nd in the following range, the absolute value of the curvature of the optical functional surface of the lens can be reduced (relaxing the curvature of the optical functional surface of the prism) with the same light-gathering power. Whether it is precision press molding or grinding and polishing, the more relaxed the curvature of the optical functional surface of the lens, the easier it is to make, so by using high-refractive-index glass, the productivity of optical elements can be improved. Furthermore, by increasing the refractive index, it is also possible to provide a glass material suitable for optical elements used in high-function, compact optical systems.

[0112] In the optical glass 1, a preferred range of the refractive index nd is a range satisfying the following formula (2), and a more preferred range of the refractive index nd is a range satisfying the following formula (3).

[0113] nd≥1.80653-0.00459×νd···(2)

[0114] nd≥1.84303-0.00459×νd···(3)

[0115] exist Figure 1 The diagram in the figure shows the equations when the equality sign in equation (2) and equation (3) holds respectively.

[0116] The optical glass 1 preferably exhibits positive anomalous dispersion. Anomalous dispersion can be quantitatively expressed using ΔPg,F. The relative partial dispersion Pg,F can be calculated using the refractive indices ng, nF, and nC at the g-line, F-line, and C-line, using the formula (1) (Pg,F = (ng-nF) / (nF-nC)) shown above.

[0117] As commercially available low-dispersion glasses having an Abbe number νd of 45 or more, FCD100 and FCD515 manufactured by HOYA are known.

[0118] In a graph with the horizontal axis being the Abbe number νd and the vertical axis being the relative partial dispersion Pg,F, FCD100 is plotted at the coordinates (95.10.5334) and FCD515 is plotted at the coordinates (68.63 0.5441), and the straight line L connecting the two points is examined. This straight line L can be roughly expressed as "Pg,F = -0.0004νd + 0.5718".

[0119] exist Figure 2 A straight line L is shown in the figure.

[0120] like Figure 2 As shown, commercially available low-dispersion glass (existing glass) with an Abbe number νd of 45 or more is located on the straight line L or on the side where the relative partial dispersion Pg,F is smaller than the straight line L in the Abbe number νd-relative partial dispersion Pg,F graph.

[0121] In a preferred embodiment of the optical glass 1 , the Abbe number νd and the relative partial dispersion Pg,F satisfy the following formula (4).

[0122] Pg,F>-0.0004νd+0.5718···(4)

[0123] An optical glass having an Abbe number νd of 45 or more and satisfying the above formula (4) has a large relative partial dispersion Pg,F relative to a specific Abbe number νd and is suitable as an optical glass for correcting high-order chromatic aberrations.

[0124] (Transmittance)

[0125] The optical glass 1 is preferably slightly colored and is suitable as a material for an optical element for imaging such as a camera lens and an optical element for projection such as a projector.

[0126] A preferred embodiment of the optical glass 1 is a glass having an internal transmittance of 96.5% or more at a wavelength of 400 nm to 700 nm and a thickness of 10 mm.

[0127] The internal transmittance is preferably in a range of 97% or more, more preferably in a range of 98% or more, and still more preferably in a range of 99% or more.

[0128] In addition, laser glass and other glasses containing luminescent ions such as Nd, Eu, Er, V, etc. have absorption in the visible light region and are therefore not suitable for use as materials for optical elements for imaging such as camera lenses and optical elements for projection such as projectors.

[0129] (Glass transition temperature Tg)

[0130] The preferred embodiment of the optical glass 1 is an optical glass having a glass transition temperature Tg of 550°C or less. When the glass transition temperature is low, the heating temperature when the glass is reheated and softened for press molding can be reduced. As a result, it is easy to suppress the fusion of the glass and the press molding mold. In addition, since the heating temperature can be reduced, the heat consumption of the glass heating device, the press molding mold, etc. can also be reduced. Furthermore, the annealing temperature of the glass can also be reduced, so the life of the annealing furnace can be extended. The more preferred range of the glass transition temperature is below 530°C, and the further preferred range is below 500°C.

[0131] (Liquidus temperature)

[0132] A preferred embodiment of the optical glass 1 is an optical glass having a liquidus temperature of 850° C. or less. When the liquidus temperature is low, the melting and molding temperatures of the glass can be lowered. As a result, the volatility of the glass during melting and molding can be reduced, and the generation of streaks and changes in optical properties can be suppressed.

[0133] A more preferred range of the liquidus temperature is 800°C or lower, and a further preferred range is 750°C or lower.

[0134] (proportion)

[0135] The optical glass 1 can be obtained by mainly containing Nb without relying on rare earth which increases the relative partial dispersion but also increases the specific gravity. 5+ While increasing the relative partial dispersion, the proportion of fluorophosphate glass with large relative partial dispersion is relatively small.

[0136] A preferred embodiment of the optical glass 1 is an optical glass having a specific gravity of 4.2 or less. By reducing the specific gravity, the optical element can be made lighter.

[0137] The more preferred range of the specific gravity is 4.1 or less, and the further preferred range is 4 or less.

[0138] [Optical glass 2]

[0139] Hereinafter, the optical glass 2 which is one embodiment of the present invention will be described.

[0140] <Glass Characteristics>

[0141] The Abbe number νd and relative partial dispersion Pg,F of the above-mentioned optical glass 2 satisfy the following formula (4).

[0142] Pg,F>-0.0004νd+0.5718···(4)

[0143] The optical glass 2 whose Abbe number νd and relative partial dispersion Pg,F satisfy the above formula (4) is suitable as an optical glass for correcting high-order chromatic aberration.

[0144] In addition, in the optical glass 2, from the perspective of effectively utilizing the anomalous partial dispersion, the Abbe number νd is preferably in the range of 45 or more. The preferred upper limit of the Abbe number νd is 80, and the more preferred upper limit is 70. On the other hand, in order to effectively utilize the low dispersion, the more preferred lower limit of the Abbe number νd is 50, and the further preferred lower limit is 55.

[0145] <Chemical durability>

[0146] (D NaOH )

[0147] The optical glass 2 has a mass reduction per unit area when immersed in a NaOH aqueous solution for 15 hours. NaOH Less than 0.25mg / (cm 2 ·15h) chemical durability.

[0148] The above mass reduction D NaOH It can be obtained by the following method.

[0149] First, prepare a disk-shaped glass sample with a diameter of 43.7 mm and a thickness of 5 mm. The two opposite surfaces of the diameter of 43.7 mm are double-sided polished, and the side surfaces are masked by laminating a tape (e.g., a polyimide tape, etc.) that is chemically durable to the aqueous solution of sodium hydroxide (NaOH) described below. Therefore, the above two surfaces of the disk-shaped glass sample are exposed to the aqueous solution of sodium hydroxide (NaOH) described below. The total area of ​​these two surfaces (hereinafter, referred to as "the surface area of ​​the glass sample") is 30 cm 2 .

[0150] Next, the mass M of the glass sample is measured. before After that, the glass sample was immersed in a well-stirred aqueous solution of sodium hydroxide (NaOH) at a liquid temperature of 50° C. and a concentration of 0.01 mol / l for 15 hours, and the mass M of the glass sample after immersion was measured. after. Quality difference before and after immersion (M before -M after ) (unit: mg) divided by the surface area of ​​the glass sample is D NaOH That is, through “(M before -M after ) / 30” and the value obtained is D NaOH .

[0151] The optical glass 2 has D NaOH Less than 0.25mg / (cm 2 ·15h) chemical durability. NaOH Optical glass can suppress the degradation of surface quality due to the appearance of potential scratches. From the perspective of maintaining high surface quality, D NaOH Preferably less than 0.20 mg / (cm 2 ·15h), more preferably less than 0.10mg / (cm 2 ·15h). NaOH The lower limit of is not particularly limited, and can be considered to be, for example, 0.02 mg / (cm 2 15h) or more as a benchmark.

[0152] (About D A )

[0153] The optical glass 2 preferably has D A Less than 0.35% chemical durability.

[0154] D A The acid resistance weight reduction rate Da is measured according to the method for measuring the acid resistance weight reduction rate Da specified in the Japan Optical Glass Industry Association Standard JOGIS06-2009. Specifically, the measuring method is as follows.

[0155] The mass equivalent to the specific gravity (M before , unit: g) was placed in a platinum basket, immersed in 80 ml of a 0.01 mol / l nitric acid aqueous solution in a quartz glass round-bottom flask, and treated in boiling water for 60 minutes. The mass M of the treated powdered glass was measured. after (Unit: g) The value (M) is obtained by dividing the difference in mass of the powder glass before and after the above treatment by the mass of the powder glass before the treatment. before -M after ) / M before The results expressed as a percentage [(M before -M after ) / M before ]×100 is D A . D with the above range AThe optical glass is suitable as a glass material for optical elements equipped in outdoor surveillance cameras and vehicle-mounted cameras that require excellent acid resistance.

[0156] D A The lower limit of is not particularly limited, and for example, 0.20% or more can be considered as a guideline.

[0157] (About D STPP )

[0158] The optical glass 2 preferably has D STPP Less than 0.40mg / (cm 2 h) Chemical durability.

[0159] D STPP The determination method is as follows.

[0160] First, a disk-shaped glass sample with a diameter of 43.7 mm and a thickness of 5 mm is prepared. The two opposite surfaces with a diameter of 43.7 mm are double-sided polished, and the side surfaces are masked by laminating a tape (e.g., a polyimide tape, etc.) that is chemically durable to the aqueous solution of sodium tripolyphosphate described below. Therefore, the above two surfaces of the disk-shaped glass sample are exposed to the aqueous solution of sodium tripolyphosphate described below. The total area of ​​these two surfaces (the surface area of ​​the glass sample) is 30 cm 2 .

[0161] Next, the mass M of the glass sample is measured. before Then, in a solution of sodium tripolyphosphate (Na 5 P 3 O 10 ) in an aqueous solution for 1 hour, and the mass M of the glass sample after immersion is measured. after The mass difference before and after immersion (M before -M after The value of (unit: mg) divided by the surface area of ​​the glass sample and the immersion time is defined as D STPP That is, through “(M before -M after ) / (30×1)” and the value obtained is D STPP .

[0162] The optical glass 2 preferably has D STPP Less than 0.20mg / (cm 2 h) Chemical durability. STPP The lower limit of is not particularly limited, and can be considered to be, for example, 0.02 mg / (cm 2 h) The above is used as a benchmark.

[0163] By making DSTPP When the content is within the above range, the occurrence of a decrease in surface quality can be further suppressed.

[0164] Regarding other glass properties of the optical glass 2, one or more of the above items described for the optical glass 1 may be used in any combination. In addition, regarding the glass properties of the optical glass 1, one or more of the above items described for the optical glass 2 may be used in any combination.

[0165] (D 0 )

[0166] In the above optical glass 2, D is preferred 0 Less than 5.0×10 -3 mg / (cm 2 h). 0 Sometimes also referred to as true chemical durability in water.

[0167] D 0 The determination method is as follows.

[0168] First, prepare a disk-shaped glass sample with a diameter of 43.7 mm and a thickness of 5 mm. The two opposite surfaces of the diameter of 43.7 mm are double-sided polished, and the side surfaces are masked by laminating a tape (e.g., a polyimide tape, etc.) that is chemically durable to the following pure water. Therefore, the above two surfaces of the disk-shaped glass sample are exposed to the following pure water. The total area of ​​these two surfaces (the surface area of ​​the glass sample) is 30 cm 2 .

[0169] Next, the mass M of the glass sample is measured. before After that, the glass sample is immersed in pure water which is circulated through an ion exchange resin at a rate of 1 liter per minute, maintained at a water temperature of 50°C, pH = 7.0 ± 0.2, and stirred thoroughly. The mass M of the glass sample after being immersed in the above pure water for more than 20 hours (preferably more than 40 hours) is measured. after The mass difference before and after immersion (M before -M after The value of (unit: mg) divided by the surface area of ​​the glass sample and the immersion time is defined as D 0 That is, through “(M before -M afte r ) / (30×immersion time (unit: hour))” and the value obtained is D 0 .

[0170] By making D 0 By being within the above range, it is possible to suppress the degradation of the surface quality of the glass under cleaning or high humidity environment. 0There is no particular lower limit for the -3 mg / (cm 2 h) The above is used as a benchmark.

[0171] <Glass Composition>

[0172] The optical glass 2 preferably contains Nb 5+ .

[0173] Nb 5+ It has the effect of increasing the relative partial dispersion and improving the chemical durability, especially D NaOH and D A In order to achieve this effect, Nb 5+ The preferred range of the content of Nb is 1.0% or more, more preferably 1.5% or more, further preferably 2% or more, further preferably 2.5% or more, and further preferably 3% or more. 5+ , the thermal stability of the glass can be maintained. From the perspective of suppressing the volatility of the glass during melting, Nb 5+ The preferred upper limit of the content is 15%.

[0174] Due to Al 3+ and Nb 5+ All contribute to improving chemical durability. Therefore, from the perspective of imparting excellent chemical durability to glass, Al 3+ and Nb 5+ The total content of Al is preferably 10% or more, more preferably 12% or more, and further preferably 15% or more. 3+ and Nb 5+ The total content of is preferably 45% or less, more preferably 35% or less.

[0175] Regarding other glass compositions of the optical glass 2, one or more of the above items described for the optical glass 1 may be used in any combination. In addition, regarding the glass composition of the optical glass 1, one or more of the above items described for the optical glass 2 may be used in any combination.

[0176] <Method for manufacturing glass>

[0177] The optical glasses 1 and 2 can be obtained by, for example, mixing, melting, and molding glass raw materials in a manner that can obtain desired properties. As glass raw materials, for example, phosphates, fluorides, alkali metal compounds, alkaline earth metal compounds, etc. can be used. The melting method and molding method of the glass can use known methods.

[0178] [Glass material for press molding, method for producing the same, and method for producing a glass molded body]

[0179] According to one embodiment of the present invention, there can be provided a press-molding glass material formed of the optical glass 1 or the optical glass 2, a glass molded body formed of the optical glass, and methods for producing the same.

[0180] The press-molding glass material means a glass block that is heated and subjected to press molding.

[0181] Examples of press-molding glass materials include glass blocks having a mass equivalent to that of press-molded products, such as precision press-molding preforms and glass materials for press-molding optical element blanks (press-molding glass gobs).

[0182] The glass material for press molding can be produced by a process of processing a glass molded body. The glass molded body can be produced by heating and melting glass raw materials as described above and molding the obtained molten glass. Examples of the processing method of the glass molded body include cutting, grinding, polishing, etc.

[0183] [Optical element blank and method for manufacturing the same]

[0184] According to one embodiment of the present invention, an optical element blank formed of the optical glass 1 or the optical glass 2 can be provided. The optical element blank is a glass molded body having a shape similar to the shape of the optical element to be manufactured. The optical element blank can be manufactured by a method of molding glass into a shape obtained by adding a machining allowance removed due to machining to the shape of the optical element to be manufactured. The optical element blank can be manufactured by, for example, a method of press molding by heating and softening a glass material for press molding (secondary press molding method); a method of press molding by supplying a molten glass block to a press molding mold using a known method (direct press molding method); and the like.

[0185] [Optical element and method of manufacturing the same]

[0186] According to one embodiment of the present invention, an optical element formed by the above-mentioned optical glass 1 or the above-mentioned optical glass 2 can be provided. As the type of optical element, examples include: lenses such as spherical lenses and aspherical lenses, prisms, diffraction gratings, etc. As the shape of the lens, examples include: various shapes such as biconvex lenses, plano-convex lenses, biconcave lenses, plano-concave lenses, convex-mirror concave-convex lenses, and concave-mirror concave-convex lenses. The optical element can be manufactured by a method including a step of processing a glass molded body formed by the above-mentioned optical glass. As processing, examples include: cutting, machining, rough grinding, fine grinding, polishing, etc. When the above-mentioned glass is used in such processing, breakage can be reduced, and high-quality optical elements can be stably supplied.

[0187] [Example]

[0188] Hereinafter, the present invention will be described in further detail by way of examples, but the present invention is not limited to the embodiments shown in the examples.

[0189] (Example 1)

[0190] Phosphates, fluorides, oxides, etc. corresponding to the respective glass compositions were used as raw materials for introducing the respective components so as to obtain the glass compositions shown in Table 1. The raw materials were weighed and sufficiently mixed to prepare blended raw materials.

[0191] The blended raw materials were added to a platinum crucible, heated and melted. After melting, the molten glass was poured into a casting mold, placed and cooled to near the glass transition temperature and immediately placed in an annealing furnace, annealed for about 1 hour in the glass transition temperature range, and then placed in a furnace and cooled to room temperature, thereby obtaining the optical glasses shown in Table 1.

[0192] The obtained optical glass was observed under an optical microscope, and as a result, no crystal precipitation, foreign matter such as platinum particles, bubbles, or striae were observed.

[0193] Table 1 shows the properties of the optical glass obtained in this manner.

[0194] The various properties of the optical glass were measured by the methods shown below.

[0195] (1) Refractive index nd, ng, nF, nC and Abbe number νd

[0196] The refractive index nd, ng, nF, nC and Abbe number νd of the glass obtained by cooling at a cooling rate of -30°C / hour were measured using a refractive index measurement method in accordance with the Japan Optical Glass Industries Association standard.

[0197] In addition, Figure 1 In the figure, the Abbe number νd and the refractive index nd of each of the above optical glasses are plotted.

[0198] (2) Relative partial dispersion Pg,F and the deviation of Pg,F from the standard line ΔPg,F

[0199] The relative partial dispersion Pg,F is calculated from the refractive indices ng, nF, and nC, and the deviation ΔPg,F from the relative partial dispersion Pg,F(0) on the standard line calculated from the Abbe number νd is calculated.

[0200] Table 1 shows the refractive index nd, the Abbe number νd, and Pg,F and ΔPg,F calculated from ng, nF, and nC.

[0201] In addition, Figure 2 In the figure, the Abbe number νd and relative partial dispersion Pg,F of the above optical glasses are plotted.

[0202] (3) Glass transition temperature Tg

[0203] The glass transition temperature Tg was measured at a temperature increase rate of 10° C. / min using a differential scanning calorimeter (DSC3300) manufactured by NETZSCH.

[0204] (4) Liquidus temperature LT

[0205] 50 g of glass was placed in a platinum crucible, covered with a platinum lid, and melted at 1100°C for 20 minutes, and then kept at a predetermined temperature for 2 hours. The glass after being kept for 2 hours was observed, and the liquidus temperature LT was determined based on the presence or absence of crystal precipitation.

[0206] Each of the glasses shown in Table 1 was held at 850° C. for 2 hours using the above-mentioned method, and then visually observed and observed under a magnified optical microscope (100 times), whereupon no precipitation of crystals was observed.

[0207] Therefore, the liquidus temperature LT of each glass shown in Table 1 is 850° C. or lower.

[0208] (5) Specific gravity

[0209] The specific gravity was determined by the Archimedean method.

[0210] (6) Evaluation of the reduction in volatilization during melting

[0211] A glass batch (150 to 200 g in terms of yield) is filled into a platinum crucible, covered with a platinum lid, and the mass X is measured, and then melted at 1050°C for 1.5 hours. Then, the mass Y of the platinum crucible covered with a platinum lid with the molten glass added thereto is measured again just before the molten glass is cast into a mold, and the mass change rate (XY) / X is calculated. When the glass batch is prepared in such a way that the yield becomes 150 g, X is 150 g, and when the glass batch is prepared in such a way that the yield becomes 200 g, X is 200 g.

[0212] In the case where the glass batch contains carbonates, during the melt, CO in the carbonates 2 In the case where the glass batch contains sulfates, nitrates, hydroxides, SO 3 、NO 2 , H 2 O is expelled during the melt.

[0213] The CO contained in the glass batch can be calculated in advance 2 、SO 3 、NO 2 , H 2 The glass batch is prepared in such a way that the mass X is obtained by subtracting the mass of the gas component from the mass of the glass batch.

[0214] In Table 1, A is designated as a mass change rate of 2% or less, B is designated as a mass change rate of more than 2% and 4% or less, and C is designated as a mass change rate of more than 4%.

[0215] In addition, the internal transmittance of each glass of the Examples shown in Table 1 at a thickness of 10 mm was measured according to the internal transmittance measurement method (JOGIS-17) of the Japan Optical Glass Industries Association standard. As a result, all samples had a transmittance of 96.50% or more.

[0216] (7)D NaOH

[0217] A disk-shaped glass sample (two surfaces were double-sided polished) with a diameter of 43.7 mm and a thickness of 5 mm was immersed in a well-stirred aqueous solution of sodium hydroxide (NaOH) at a liquid temperature of 50°C and a concentration of 0.01 mol / l for 15 hours. The mass reduction before and after immersion was divided by the surface area of ​​the glass sample and taken as D. NaOH .

[0218] (8)D A

[0219] Powdered glass (particle size 425 μm to 600 μm) of mass (g) equivalent to the specific gravity is placed in a platinum basket, immersed in 80 ml of 0.01 mol / l nitric acid aqueous solution in a quartz glass round-bottom flask, and treated in boiling water for 60 minutes. The percentage of the value of the mass reduction of the powdered glass before and after the treatment divided by the mass of the powdered glass before immersion is set as D A .

[0220] (9)D STPP

[0221] A glass sample with a diameter of 43.7 mm and a thickness of 5 mm was immersed in a well-stirred sodium tripolyphosphate (Na 5 P 3 O 10 ) in an aqueous solution for 1 hour, and the value of D is the mass reduction before and after immersion divided by the surface area of ​​the glass sample and the immersion time. STPP .

[0222] (10)D 0

[0223] A glass sample with a diameter of 43.7 mm and a thickness of 5 mm was immersed in pure water that was circulated through an ion exchange resin at a rate of 1 liter per minute, maintained at a temperature of 50°C, pH = 7.0 ± 0.2, and stirred thoroughly for 45 hours. The difference in mass before and after immersion was divided by the unit surface area of ​​the glass sample and the immersion time to obtain the value of D. 0 .

[0224] (Comparative Example 1)

[0225] Glass having the composition of Comparative Example 1 shown in Table 1 was prepared, and the refractive index nd, Abbe number νd, relative partial dispersion Pg,F, glass transition temperature Tg, specific gravity, and volatilization reduction during melting were evaluated according to the above method. Comparative Example 1 is a glass of a comparative example with respect to Optical Glass 1, and the volatilization reduction during melting was evaluated, and the quality change rate was greater than 4% (evaluation result C).

[0226] (Comparative Example 2)

[0227] Glass having the composition of Comparative Example 2 shown in Table 1 was prepared, and the refractive index nd, Abbe number νd, relative partial dispersion Pg,F, glass transition temperature Tg, specific gravity, volatile reduction during melting, D NaOH The evaluation results are shown in Table 1. Comparative Example 2 is a glass of a comparative example with respect to Optical Glass 2, D NaOH Greater than 0.25mg / (cm 2 ·15h), and does not satisfy formula (4).

[0228] The above results are shown in Table 1 (Table 1-1 to Table 1-7).

[0229]

Table 1-1

[0230]

[0231] (Note) In the case of positive values, the following equation is satisfied. Pg,F>-0.0004νd+0.5718

[0232] Table 1-2]

[0233]

[0234] (Note) In the case of positive values, the following equation is satisfied. Pg,F>-0.0004νd+0.5718

[0235]

Table 1-3

[0236]

[0237] (Note) In the case of positive values, the following equation is satisfied. Pg,F>-0.0004νd+0.5718

[0238]

Table 1-4

[0239]

[0240] (Note) In the case of positive values, the following equation is satisfied. Pg,F>-0.0004νd+0.5718

[0241]

Table 1-5

[0242]

[0243] (Note) In the case of positive values, the following equation is satisfied. Pg,F>-0.0004νd+0.5718

[0244]

Table 1-6

[0245]

[0246] (Note) In the case of positive values, the following equation is satisfied. Pg,F>-0.0004νd+0.5718

[0247]

Table 1-7

[0248]

[0249] (Note) In the case of positive values, the following equation is satisfied. Pg,F>-0.0004νd+0.5718

[0250] The glass compositions of the examples in Table 1 expressed in atomic % are shown in Table 2 (Table 2-1 to Table 2-3).

[0251]

[0252]

[0253]

[0254] (Example 2)

[0255] The optical glasses of Example 1 were used to produce lens blanks according to the known method. The produced lens blanks were ground and polished to produce various lenses (biconvex lens, convex concave-convex lens, concave concave-convex lens, biconcave lens, plano-convex lens, plano-concave lens).

[0256] All lenses are lightweight and suitable for high-order chromatic aberration correction.

[0257] Finally, the above methods are summarized.

[0258] According to one embodiment, an optical glass 1 is provided. The optical glass 1 includes P 5+ 、Al 3+ , Nb 5+ , O 2- and F - As an essential ingredient, Al 3+ The content relative to P 5+ The molar ratio of the content (Al 3+ / P 5+ ) is 0.30 or more, Nb 5+ The content of cation is 1.0% or more, O 2- The content is 10-85% anion, F - The content of anions is 15-90%, O 2- The content relative to P 5 + and Nb 5+ The molar ratio of the total content (O 2- / (P 5+ +Nb 5+ )) is above 3.0.

[0259] In one embodiment, the optical glass 1 may include at least one selected from Mg 2+ , Ca 2+ , Sr 2+ And Ba 2+ Alkaline earth metal components, Mg 2+ , Ca 2+ , Sr 2+ And Ba 2+ The total content is 20 cationic % or more.

[0260] In one embodiment, P of the optical glass 1 5+ The content of Al can be 5-40% cations. 3+ The content can be 5 to 30 cation %.

[0261] In one embodiment, the molar ratio of the optical glass 1 is ( 2- / (P 5+ +Nb 5+)) can be below 4.0.

[0262] In one embodiment, the optical glass 1 may include at least one selected from La 3+ , Gd 3+ , Y 3+ 、Lu 3+ Yb 3+ Rare earth components in 3+ , Gd 3+ , Y 3+ 、Lu 3+ Yb 3+ Total content (La 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ ) relative to Al 3+ The molar ratio of the content (La 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ ) / Al 3+ ) can be less than 0.3.

[0263] According to one embodiment, there is provided an optical glass 2, wherein the optical glass 2 is made of fluorophosphate glass and has a mass reduction D per unit area when immersed in a NaOH aqueous solution for 15 hours. Na OH Less than 0.25mg / (cm 2 ·15h), and the Abbe number νd and the relative partial dispersion Pg,F satisfy the above formula (4).

[0264] According to one embodiment, D of the optical glass 2 A Can be less than 0.35%.

[0265] According to one embodiment, D of the optical glass 2 STPP Can be less than 0.40mg / (cm 2 h).

[0266] According to one embodiment, D of the optical glass 2 0 Can be less than 5.0×10 -3 mg / (cm 2 h).

[0267] According to one embodiment, the optical glass 2 may contain Nb 5+ .

[0268] According to one embodiment, the optical glass 2 may contain 1.0% or more of Nb. 5+ .

[0269] According to one embodiment, Nb in the optical glass 2 is 5+ The content of can be 15% or less.

[0270] According to one embodiment, the Al in the optical glass 2 3+ and Nb 5+ The total content of can be 10% or more.

[0271] According to one embodiment, the P of the optical glass 2 5+ The content can be 5 to 40%.

[0272] According to one embodiment, the Al in the optical glass 2 3+ The content can be 5 to 40%.

[0273] According to one embodiment, the Mg content of the optical glass 2 is 2+ The content can be 0 to 10%.

[0274] According to one embodiment, Ca of the optical glass 2 2+ The content can be 0 to 20%.

[0275] According to one embodiment, the Sr of the optical glass 2 2+ The content can be 0 to 40%.

[0276] According to one embodiment, Ba of the optical glass 2 2+ The content can be 5 to 40%.

[0277] According to one embodiment, the La of the optical glass 2 3+ The content can be 0 to 5%.

[0278] According to one embodiment, the Gd in the optical glass 2 3+ The content can be 0 to 5%.

[0279] According to one embodiment, Y of the optical glass 2 3+ The content can be 0 to 5%.

[0280] According to one embodiment, Lu of the optical glass 2 3+ The content can be 0 to 5%.

[0281] According to one embodiment, Yb in the optical glass 2 3+ The content relative to La 3+ , Gd 3+ , Y 3+ 、Lu 3+ Yb 3+ The molar ratio of the total content (Yb 3+ / (La3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ )) can be below 0.5.

[0282] According to one embodiment, Zn in the optical glass 2 2+ The content can be 0 to 10%.

[0283] According to one embodiment, the total content of the alkali metal components in the optical glass 2 may be 0 to 30%.

[0284] According to one embodiment, Rb of the optical glass 2 + The content can be 0 to 1%.

[0285] According to one embodiment, the Cs of the optical glass 2 is + The content can be 0 to 1%.

[0286] According to one embodiment, the Li of the optical glass 2 + The content can be 0 to 30%.

[0287] According to one embodiment, the Li of the optical glass 2 + The content of can be 2% or more.

[0288] According to one embodiment, the Li of the optical glass 2 + The content can be 4 to 10%.

[0289] According to one embodiment, the Na content of the optical glass 2 is + The content can be 0 to 10%.

[0290] According to one embodiment, the K of the optical glass 2 is + The content can be 0 to 10%.

[0291] According to one embodiment, the Si of the optical glass 2 4+ The content can be 0 to 5%.

[0292] According to one embodiment, B of the optical glass 2 3+ The content of can be 2% or less.

[0293] According to one embodiment, Cl of the optical glass 2 - The content can be 0 to 1%.

[0294] According to one embodiment, the Sb in the optical glass 2 3+ and Ce 4+ The total content of can be 0% or more and can be less than 1%.

[0295] According to one embodiment, the optical glass 2 may substantially not contain at least one of Pb, Cd, As, and Th species.

[0296] According to one embodiment, the optical glass 2 may substantially not contain at least one of Cu, Co, Ni, Fe, Cr, Eu, Nd, Er, and V.

[0297] According to one embodiment, the optical glass 2 may substantially not contain at least one of Hf, Ga, Ge, Te, and Tb.

[0298] According to one embodiment, the Abbe number νd of the optical glass 2 can be 45 or more.

[0299] According to one embodiment, the Abbe number νd of the optical glass 2 can be 80 or less.

[0300] According to one embodiment, the refractive index nd and the Abbe number νd of the optical glass 2 can satisfy the following formula (2).

[0301] nd≥1.80653-0.00459×νd···(2)

[0302] According to one embodiment, the refractive index nd and the Abbe number νd of the optical glass 2 can satisfy the following formula (3).

[0303] nd≥1.84303-0.00459×νd···(3)

[0304] According to one embodiment, the optical glass 2 may have an internal transmittance of 96.5% or more at a wavelength of 400 nm to 700 nm and a thickness of 10 mm.

[0305] According to one embodiment, the glass transition temperature Tg of the optical glass 2 can be 550° C. or lower.

[0306] According to one embodiment, the liquidus temperature of the optical glass 2 can be 850° C. or lower.

[0307] According to one embodiment, the specific gravity of the optical glass 2 may be 4.2 or less.

[0308] According to another embodiment, an optical element formed of the optical glass 1 or the optical glass 2 is provided.

[0309] The embodiments disclosed herein are illustrative in all aspects and should not be construed as limiting. The scope of the present invention is indicated by the scope of the claims rather than the above description, and is intended to include all changes within the meaning and scope equivalent to the scope of the claims.

[0310] For example, the optical glass of one embodiment of the present invention can be obtained by adjusting the composition described in the specification about the glass composition exemplified above.

[0311] Furthermore, it is of course possible to arbitrarily combine two or more items described as examples or preferred ranges in the specifications.

Claims

1. An optical glass comprising P 5+ 、Al 3+ , Nb 5+ , O 2- and F - As a necessary ingredient, Al 3+ The content relative to P 5+ The molar ratio of Al 3+ / P 5+ is 0.30 or more, Nb 5+ The content of cation is 1.0% or more, O 2- The content of anion is 10~85% F - The content of anion is 15-90%, O 2- The content relative to P 5+ and Nb 5+ The molar ratio of the total content of 2- / (P 5+ +Nb 5+ ) is 3.0 or more.

2. The optical glass according to claim 1, in, Contains at least one selected from Mg 2+ , Ca 2+ , Sr 2+ And Ba 2+ The alkaline earth metal components in Mg 2+ , Ca 2+ , Sr 2+ And Ba 2+ The total content is 20 cationic % or more.

3. The optical glass according to claim 1 or 2, in, P 5+ The content of cations is 5-40%, Al 3+ The content is 5 to 30 cation %.

4. The optical glass according to any one of claims 1 to 3, in, Molar Ratio 2- / (P 5+ +Nb 5+ ) is less than 4.

0.

5. The optical glass according to any one of claims 1 to 4, in, Contains at least one selected from La 3+ , Gd 3+ , Y 3+ 、Lu 3+ Yb 3+ The rare earth components in La 3+ , Gd 3+ , Y 3+ 、Lu 3+ Yb 3+ Total content (La 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ ) relative to Al 3+ The molar ratio of the content (La 3+ +Gd 3+ +Y 3+ +Lu 3+ +Yb 3+ ) / Al 3+ Is less than 0.

3.

6. An optical glass formed of fluorophosphate glass, The mass reduction per unit area when immersed in NaOH aqueous solution for 15 hours D NaOH Less than 0.25mg / (cm 2 15h), and The Abbe number νd and the relative partial dispersion Pg,F satisfy the following equation (4): Pg,F>-0.0004νd+0.5718···(4). 7 . An optical element formed of the optical glass according to claim 1 .

Citation Information

Patent Citations

  • Fluorophosphate optical glass having high positive abnormal part of dispersion value delta ve of *10*0 to *21*0 * comparatively high refraction index of 1*47 to 1*54 and abbe number of 84*1 to 51*0

    JP1976114412A

  • Niobium oxide-containing formable fluorophosphate glass

    JP1983217451A

  • Optical glass having small photoelastic constant

    JP2005112717A

  • Optical glass, optical element and preform

    JP2013151410A